IMPACT OF USING PROPHYLACTIC ANTIBIOTIC ON PREVENTION OF WOUND INFECTION IN INGUINAL HERNIORRHAPHY: Prophylactic Antibiotic in Inguinal Herniorrhaphy - Akhtar, Kaleem; Khan, Zakaullah; Bhatti, Ahsan Manzoor; Mahmood, Khalid (Pakistan Armed Forces Medical Journal, 2015)
Objective: To compare the effect of antibiotic prophylaxis with placebo in prevention of wound infection amongst patients undergoing clean open inguinal herniorrhaphy (without mesh). Study Design: Randomized Controlled Trial. Place and Duration of Study: Pakistan Air Force Hospital, Faisal Base Karachi from October 2009 to November 2011. Material and Methods: One hundred and fifty patients undergoing inguinal herniorrhaphy were included and randomly assigned to one of the two groups using random numbers table. Group A patients were given intravenous antibiotic while those in Group B were given equal volume of normal saline just before the induction of anaesthesia. Patients from both groups were observed for the presence of wound infection. Results: Total seven cases (4.7%) of surgical site infection were detected; two cases (2.7%) occurred in group A whereas five cases (6.7%) occurred in group B. The low frequency of post-operative wound infection was seen in group A as compared to group B but the difference was statistically insignificant. Conclusion: Antibiotic prophylaxis has no signiﬁcant effect on prevention of wound infection in inguinal herniorrhaphy.